2017
DOI: 10.1523/eneuro.0311-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology Reveals the Neural Dynamics of Naturalistic Auditory Language Processing: Event-Related Potentials Reflect Continuous Model Updates

Abstract: The recent trend away from ANOVA-based analyses places experimental investigations into the neurobiology of cognition in more naturalistic and ecologically valid designs within reach. Using mixed-effects models for epoch-based regression, we demonstrate the feasibility of examining event-related potentials (ERPs), and in particular the N400, to study the neural dynamics of human auditory language processing in a naturalistic setting. Despite the large variability between trials during naturalistic stimulation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 83 publications
(111 reference statements)
0
56
0
Order By: Relevance
“…Nonetheless, the naturalistic paradigms remain crucial for understanding speech and language processing in its full complexity, where interactions between both local linguistic and global contextual features, both linguistic (cf. Alday, Schlesewsky, & Bornkessel-Schlesewsky, 2017) and paralinguistic (Tromp, Peeters, Meyer, & Hagoort, 2017), matter as well as their constant, continuous overlap (cf. Steinberg, Truckenbrodt, & Jacobsen, 2012, who found that stimulus splicing and the resultant misleading formant transitions impact phonological processing).…”
Section: Intentional Omissionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, the naturalistic paradigms remain crucial for understanding speech and language processing in its full complexity, where interactions between both local linguistic and global contextual features, both linguistic (cf. Alday, Schlesewsky, & Bornkessel-Schlesewsky, 2017) and paralinguistic (Tromp, Peeters, Meyer, & Hagoort, 2017), matter as well as their constant, continuous overlap (cf. Steinberg, Truckenbrodt, & Jacobsen, 2012, who found that stimulus splicing and the resultant misleading formant transitions impact phonological processing).…”
Section: Intentional Omissionsmentioning
confidence: 99%
“…The authors used ridge regression to calculate the TRF and found a negativity with a latency and distribution corresponding to a traditional N400. Broderick and colleagues hesitated to use the N400 label, however, as they had no cloze probability manipulation; nonetheless, in light of more recent N400 perspectives (Kutas & Federmeier, 2011) beyond discrete components (Alday et al, 2017), the resulting component can safely be classified as an N400. Furthermore, noise and cocktail-party attention manipulations attenuated this response.…”
Section: Scaling Up: Using Modern Statistical and Computational Appromentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to traditional null-hypothesis significance testing, i.e. repeated-measures ANOVAs, multilevel models do not only address the potential significance of a difference between conditions but estimate the difference itself (for more information about multilevel modelling see Alday, Schlesewsky, & Bornkessel-Schlesewsky, 2017; for general information regarding estimation see Cumming, 2014) (Alday et al, 2017). Parameters estimates can be interpreted as statistically significant (in line with traditional null-hypothesis significance testing) if their credible intervals do not contain zero.…”
Section: Statistical Analysesmentioning
confidence: 99%